Chemosensitivity and chemoresistance in endometriosis – differences for ectopic versus eutopic cells. Issue 4 (October 2019) - Lavogina, Darja; Samuel, Külli; Lavrits, Arina; Meltsov, Alvin; Sõritsa, Deniss; Kadastik, Ülle; Peters, Maire; Rinken, Ago; Salumets, Andres
ABSTRACT: Research question: Endometriosis is a common gynaecological disease defined by the presence of endometrium-like tissue outside the uterus. This complex disease, often accompanied by severe pain and infertility, causes a significant medical and socioeconomic burden; hence, novel strategies are being sought for the treatment of endometriosis. Here, we set out to explore the cytotoxic effects of a panel of compounds to find toxins with different efficiency in eutopic versus ectopic cells, thus highlighting alterations in the corresponding molecular pathways. Design: The effect on cellular viability of 14 compounds was established in a cohort of paired eutopic and ectopic endometrial stromal cell samples from 11 patients. The biological targets covered by the panel included pro-survival enzymes, cytoskeleton proteins, the proteasome and the cell repair machinery. Results: Protein kinase inhibitors GSK690693, ARC-775 and sorafenib, proteasome inhibitor bortezomib, and microtubule-depolymerizing toxin monomethyl auristatin E were more effective in eutopic cells. In contrast, 10 µmol/l of the anthracycline toxin doxorubicin caused cellular death in ectopic cells more effectively than in eutopic cells. The large-scale sequencing of mRNA isolated from doxorubicin-treated and control cells indicated different survival strategies in eutopic versus ectopic endometrium. Conclusions: Overall, the results confirm evidence of large-scale metabolic reprogramming in endometriotic cells, which underlies the observed differences in sensitivity towards toxins. The enhanced efficiency of doxorubicin interfering with redox equilibria and/or DNA repair mechanisms pinpoints key players that can be potentially used to selectively target ectopic lesions in endometriosis.